2017
DOI: 10.14429/djlit.37.3.10692
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of E-books in Science & Technology: An Analytical Study of Directory of Open Access Books

Abstract: A detailed study of e-books in Science and Technology indexed in Directory of Open Access Books (DOAB) till May 15, 2016 is presented. Open access publishers, licenses and language-wise distribution of e-books indexed in DOAB is examined. The data collected only on the subjects listed in DDC-23 under Science and Technology domain. The results depicts that there are 1052 e-books indexed in Science and Technology in DOAB. The collection includes e-books that are both made-digital and born digital. Maximum books … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A total number of 35 books had been found in the field of Library and Information Science, in which 22 books had been published in the English language and registered under the CC licenses. Khanchandani & Kumar (2017) conducted a study on e-books in Science and Technology available in the DOAB. The results revealed that there were 1052 e-books indexed in the DOAB in Science and Technology disciplines, in which fewer books were available in pure sciences and more in applied sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A total number of 35 books had been found in the field of Library and Information Science, in which 22 books had been published in the English language and registered under the CC licenses. Khanchandani & Kumar (2017) conducted a study on e-books in Science and Technology available in the DOAB. The results revealed that there were 1052 e-books indexed in the DOAB in Science and Technology disciplines, in which fewer books were available in pure sciences and more in applied sciences.…”
Section: Literature Reviewmentioning
confidence: 99%